2020
DOI: 10.1155/2020/9681530
|View full text |Cite
|
Sign up to set email alerts
|

Research on a LADRC Strategy for Trajectory Tracking Control of Delta High-Speed Parallel Robots

Abstract: In order to better track the planned trajectory of Delta high-speed parallel robot, this paper proposes a dynamics control strategy for Delta high-speed parallel robots based on the linear active disturbance rejection control (LADRC) strategy which realizes decoupling control through observing and compensating the coupling and internal and external disturbances between the three joints. Firstly, the structure and dynamics model of the Delta high-speed parallel robot are analyzed, respectively. Secondly, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…For example, path-following control of AUV based on LADRC was highly robust to internal and external disturbances caused by factors such as changes in system parameters (Lamraoui and Zhu, 2018). Liu et al (2020) applied LADRC to the dynamic control of a Delta high-speed parallel robot and demonstrated that the robot has fast and accurate tracking performance at high speeds without being affected by the uncertainties of the system. But LADRC reduces part of the control performance while the parameters are simplified.…”
Section: Proposed Anmentioning
confidence: 99%
“…For example, path-following control of AUV based on LADRC was highly robust to internal and external disturbances caused by factors such as changes in system parameters (Lamraoui and Zhu, 2018). Liu et al (2020) applied LADRC to the dynamic control of a Delta high-speed parallel robot and demonstrated that the robot has fast and accurate tracking performance at high speeds without being affected by the uncertainties of the system. But LADRC reduces part of the control performance while the parameters are simplified.…”
Section: Proposed Anmentioning
confidence: 99%
“…The results show that compared with the proportional–integral controller, the grid-connected inverter using LADRC has better adaptability, robustness, and dynamic performance to the weak power grid. In Liu et al (2020), LADRC is proposed to solve the problem of accurately tracking the planned trajectory of delta high-speed parallel robots. The internal coupling and disturbance of the robot are observed and compensated by the state observer to solve the problem of strong couplings in the system.…”
Section: Introductionmentioning
confidence: 99%
“…As a new tool of operation, production and service in today's society, it plays an important role in saving labor, optimizing production mode and improving the efficiency of economic development, and greatly reduces the danger in some special types of work 4 . According to different fields, the problem background and application scenarios faced by robots are different, but in the process of motion control of mobile robots in any application scenario, it is necessary to ensure that mobile robots can track a given trajectory or target quickly and stably in the process of motion so as to realize real-time trajectory tracking control 5 .…”
Section: Introductionmentioning
confidence: 99%